Three new Assamiidae (Arachnida: Opiliones) from Cameroon, with a redescription of Chilon robustus and comments on related species - Bauer, Christian; Prieto, Carlos E. (Zootaxa, 2009)
Assamiids from a small collection at the MRAC in Tervuren provided four species represented with males: Chilon robustus Sørensen, 1896, Ereca treses sp. nov. (Erecinae), Bueana vitteli sp. nov. (Polycoryphinae) and Rhabdopygus puylaerti sp. nov. (Hypoxestinae). The revision of syntypes of several related species allowed us to revalidate Chilon undulatus Sørensen, 1896 and to postulate that Rhabdopygus maculatus Roewer, 1935 does not belong to Rhabdopygus.